Designing and Evaluating Criteria for Sustainable Supply Chain at PT. Panca Putra Galvalume Steel Kediri - Lolyka Dewi Indrasari; Silvi Rushanti Widodo; Debrina Puspita Andriani (Universitas Atma Jaya Yogyakarta, 2025)
Achieving sustainability in transportation and supply chains is critical in today's competitive, environmentally conscious world. This study focuses on prioritizing factors for a sustainable Galvalume steel supply chain in Indonesia, emphasizing material availability, efficient logistics, and eco-friendly practices. A new method utilizing the Analytic Hierarchy Process (AHP) is proposed to address the balance between economic efficiency and environmental responsibility. Six criteria were identified: material availability (X1), transport choice (X2), cost-effective packaging (X3), customer service (X4), profit optimization (X5), and environmental safety (X6). Results indicate that material availability (X1) is the top priority, followed by cost-effective packaging (X3) and environmental safety (X6). The study highlights the importance of consistent decision-making in sustainable supply chain management and identifies opportunities for incorporating electric vehicles and greener transport methods in future research. Overall, this research provides actionable insights for optimizing Galvalume steel supply chains with minimal environmental impact.